Analisis Komparatif Kesesuaian Hukum Nasional Indonesia Dan Malaysia Dengan Instrumen Hukum Internasional Dalam Perlindungan Pekerja Migran - Anita Yuliastini; Yuko Fitrian (CV Rewang Rencang, 2025)
This article comparatively analyzes the alignment of Indonesian national law (Law 18/2017) and Malaysian national law (Employment Act 1955) with the International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families (ICMW). Findings indicate that Law 18/2017, driven by Indonesia's ratification of the ICMW, comprehensively adopts international protection standards. Conversely, Malaysia's Employment Act 1955, without ICMW ratification, aligns only partially, leaving significant gaps, particularly concerning non-labor rights. The difference in ratification status is the key factor driving the divergence in migrant worker protection approaches between the two countries, highlighting the challenge of legal harmonization for more effective protection.